1994
DOI: 10.1007/bf01882748
|View full text |Cite
|
Sign up to set email alerts
|

Geometric prequantization on the spin bundle based onN-symplectic geometry: The dirac equation

Abstract: We present preliminary results for a prequantization procedure that leads in a natural way to the Dirac equation. The starting point is the recently introduced n-symplectic geometry on the bundle of linear frames LM of an n-dimensional manifold M in which the Rn-valued soldering 1-form 0 on LM plays the role of the n-symplectic potential. On a 4-dimensional spacetime manifold we consider the tensorial R4@ •4-valued function ~ on LM determined by the spacetime metric tensor g as the Hamiltonian for free observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

1996
1996
2004
2004

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 6 publications
0
13
0
Order By: Relevance
“…We present here a sketch of the structure of the theory and refer the reader to the literature [5,6,12,13,14,15] for more details. See also the works of de León, Salgado et al [3] and Awane [1].…”
Section: Coordinatesmentioning
confidence: 99%
See 1 more Smart Citation
“…We present here a sketch of the structure of the theory and refer the reader to the literature [5,6,12,13,14,15] for more details. See also the works of de León, Salgado et al [3] and Awane [1].…”
Section: Coordinatesmentioning
confidence: 99%
“…n-symplectic geometry on LE is the generalized symplectic geometry that emerges upon taking the soldering 1-form θ as the generalized symplectic potential. This geometry, including the notions of n-symplectic observables, the corresponding generalized Hamiltonian vector-valued vector fields, and generalized Poisson and graded Poisson brackets, has been developed in a series of papers [5,6,12,13,14,15]. A sketch of the basic structure of the theory can be found in section 2, but let us point out here that in [14] it was shown that the fundamentals of the canonical symplectic geometry on the cotangent bundle T * E can be constructed entirely in terms of the n-symplectic geometry on LE.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper we construct an algebra of observables for covariant Lagrangian field theories using the n-symplectic theory [3,4,5,6,7,8,9] as the engine for the construction.…”
Section: Introductionmentioning
confidence: 99%
“…Remark: In references [3,4,5,6,7,8,9,15] the term n-symplectic structure refers to the two-form that is the exterior derivative of the R n -valued soldering 1-form on frame bundles or subbundles of frame bundles.…”
Section: Introductionmentioning
confidence: 99%
“…To construct S, let us consider the two-fold universal covering group GL 4 of the group GL 4 and the corresponding principal bundle LX covering the frame bundle LX [2,[15][16][17]. Note that the group GL 4 admits only infinite-dimensional spinor representations [18].…”
Section: Introductionmentioning
confidence: 99%